2014
DOI: 10.3171/2014.7.jns132688
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications of penetrating brain injury: comparison of helical CT angiography and conventional angiography

Abstract: Object The authors conducted a study to compare the sensitivity and specificity of helical CT angiography (CTA) and digital subtraction angiography (DSA) in detecting intracranial arterial injuries after penetrating traumatic brain injury (PTBI). Methods In a retrospective evaluation of 48 sets of angiograms from 45 consecutive patients with PTBI, 3 readers unaware of the DSA findings reviewed the CTA images to determine the presence or absence of arterial injuries. A fourth reader reviewed all the disagreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 16 publications
(14 reference statements)
0
28
0
Order By: Relevance
“…[10,18] According to the recently published large series on vascular complications of penetrating head injury by Bodanapally et al, [13] true incidence of vascular injuries after penetrating head injury is not clearly known because this condition is associated with a high rate of mortality before patients are able to receive medical care. These authors state that the incidence among survivors ranges from 3 to 42%, and they emphasize that previous reports mainly focus on the aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10,18] According to the recently published large series on vascular complications of penetrating head injury by Bodanapally et al, [13] true incidence of vascular injuries after penetrating head injury is not clearly known because this condition is associated with a high rate of mortality before patients are able to receive medical care. These authors state that the incidence among survivors ranges from 3 to 42%, and they emphasize that previous reports mainly focus on the aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that CT angiogram lacks the sensitivity of the digital subtraction angiogram (DSA), its ability to detect traumatic intracranial aneurysms is very accurate. [13] Risk factors for vascular injury include orbitobasal (including transorbital) entry site, subarachnoid or intraventricular hemorrhage, trajectory within 2 cm or less to the Circle of Willis [13] and blast injury with Glascow Coma Scale 8 or less. [39] These findings should prompt a DSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical managements of TPI have always been challenging due to the closeness of trauma to vital structures like foramina opticum and cavernous sinus [2]. There are several reports on the cerebrovascular complications caused by either initial injury or the surgical intervention to remove the foreign body [3]. CTA and DSA are very helpful for the preoperative surgical planning for foreign body removal and correct diagnosis of vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography is, however, an effective screening tool in identifying injury that may require neurosurgical intervention. 96 A recent extensive literature review demonstrated similar test characteristics for MRA and computed tomographic angiography (CTA) in the diagnosis of carotid and vertebral artery dissection. Sensitivity and specificity for both ranged from 50% to 100% when compared to DSA.…”
Section: Vascular Injurymentioning
confidence: 95%